Feasibility Study of Municipal Solid Waste Management System (MSW-MS) in Sidoarjo District - Matheus Bimo Aryo Prakoso; I Ketut Gunarta (Jurnal Teknik ITS, 2020)
Sidoarjo MSW-MS currently facing a problem to fulfill their needs of Municipal Solid Waste (MSW) processing, as the data shown by Dinas Lingkungan Hidup dan Kebersihan (DLHK) of Sidoarjo district stated that their service cover only 48% of Sidoarjo total area with the amount of potentially unmanaged MSW per day reach about 83% of it or equal to 1032 ton of MSW per day. In regards to this condition, there is a need to determine a new integrated approach of MSW-MS so that MSW in Sidoarjo district can be more properly managed to reduce its potential implied expense, gain potential benefits from it, and prevent potential negative impacts from improperly managed MSW. In this research, the implementation of proposed integrated MSW-MS will be carried out by a private business entity in collaboration with DLHK of Sidoarjo district in a Public Private Partnership (PPP) scheme represented in form of Business Plan Scenario (BPS). This research focused on determining the best BPS to be implemented in Sidoarjo district which targeted to optimize implied benefits from Sidoarjo District regional government perspective as its priority but still considering BPS feasibility to be implemented by related private business. This process is done by making a financial model according to the proposed BPS that are complemented with linear regression-based for its waste generation input variable and Benefit-Cost Analysis (BCA). Feasibility for each BPS implementation for private business entity perspective determined according to its financial valuation parameters value and Benefit Cost Ratio (BCR) for DLHK of Sidoarjo district perspective. Furthermore, an adjustment of several private business parameters is made according to sensitivity and incremental analysis approach to ensure the feasibility of its implementation in terms of private business entity perspective.